Ecotourism as a source of infection with Schistosoma mansoni in Minas Gerais, Brazil. Issue 1 (December 2015) - Murta, Felipe; Massara, Cristiano; Nogueira, Joyce; dos Santos Carvalho, Omar; de Mendonça, Cristiane; Pinheiro, Viviane; Enk, Martin
Abstract Background In recent years, a new pattern of schistosomiasis transmission has been described which is related to recreational activities associated with rural or ecological tourism and migratory flows and accompanying changes in social dynamics in Brazil. The objective of this report is to describe two schistosomiasis outbreaks that occurred during the practice of rural tourism in Minas Gerais, Brazil, and review this pattern of transmission within the wider context of schistosomiasis control. Findings The first outbreak was characterized by its high infection rate, showing that 59 % of the exposed eco-tourists became positive for infection withSchistosoma mansoni . In addition, all three disease transmitting species of intermediate host snails were found in the area. In the second outbreak, all members of one tourist family were infected and reported contact with water in a well-known tourist area. The malacological survey in the region revealed an infection rate withS. mansoni of 8.3 % among the collected snails. Conclusions Infection of urban dwellers that report contact with contaminated water associated with ecotourism represents a new pattern of disease transmission and dissemination. The infection with the disease at these occasions finds its expression in outbreaks of acute schistosomiasis among internal tourists to rural areas. Therefore, epidemiological surveillance in endemic areas should be aware of this schistosomiasis transmission pattern, and a multidisciplinary approach, most of all sanitation and health education measures, is required in order increase the efficiency of control strategies.